Egbert Jamieson, The Municipal Code of Chicago: Comprising the Laws of Illinois Relating to the City of Chicago, and the Ordinances of the City Council; Codified and Revised, Page 301-304, § 1264 - (:unkn) unknown (General Publisher, 1881)
Prohibited selling, keeping, or giving away any gunpowder or gun-cotton in any quantity. Violators fined twenty-five dollars for every offense.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER